In vitro anti-Pythium insidiosum activity of biogenic silver nanoparticles. (29th December 2018) - de Souza Silveira Valente, Júlia; Braga, Caroline Quintana; Brasil, Carolina Litchina; Baptista, Cristiane Telles; Reis, Guilherme Fonseca; Panagio, Luciano Aparecido; Nakazato, Gerson; de Oliveira Hübner, Silvia; Soares, Mauro Pereira; de Avila Botton, Sônia; Pereira, Daniela Isabel Brayer
Abstract: Pythium insidiosum belongs to the phylum Oomycota. It is capable of infecting mammals causing a serious condition called pythiosis, which affects mainly horses in Brazil and humans in Thailand. The objective of the present study was to verify the in vitro anti- P. insidiosum activity of a biogenic silver nanoparticle (bio-AgNP) formulation. The in vitro assays were evaluated on P. insidiosum isolates ( n = 38) following the M38-A2 protocol. Damage to the P. insidiosum hyphae ultrastructure was verified by means of scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Bio-AgNP inhibition concentrations on P. insidiosum isolates ranged from 0.06 to 0.47 μg/ml. It was observed through SEM that P. insidiosum hyphae treated showed surface roughness, as well as cell walls with multiple retraction areas, loss of continuity, and rupture in some areas. The TEM of treated hyphae did not differentiate organelle structures; also, the cellular wall was rarefied, showing wrinkled and partly ruptured borders. The bio-AgNP evaluated has excellent in vitro anti- P. insidiosum activity. However, further studies on its in vivo action are necessary as so to determine the possibility of its use in the treatment of the disease in affected hosts.